What the Buddha thought - Gombrich, Richard F. (Oxford Centre for Buddhist Studies monographs, 2009)
More about karma, and its social context -- The antecedents of the karma doctrine in Brahminism -- Jain antecedents -- What did the Buddha mean by "no soul"? -- The Buddha's positive values: love and compassion -- Assessing the evidence -- Everything is burning: the centrality of fire in the Bddha's thought -- Causation and non-random process -- Cognition; language; nirvana -- The Buddha's pragmatism and intellectual style -- The Buddha as satirist; brahmin terms as social metaphors -- Is this book to be believed?